Arsenic Trioxide in Synergy with Vitamin D Rescues the Defective VDR-PPAR-γ Functional Module of Autophagy in Rheumatoid Arthritis. (7th May 2019) - Wang, Weiyan; Li, Chunling; Zhang, Zhiyi; Zhang, Yue
Abstract : Dysregulated autophagy leads to autoimmune diseases including rheumatoid arthritis (RA). Arsenic trioxide (ATO) is a single agent used for the treatment of acute promyelocytic leukemia and is highly promising for other malignancies but is also attractive for RA, although its relationship with autophagy remains to be further clarified and its application optimized. For the first time, we report a defective functional module of autophagy comprising the Vitamin D receptor (VDR), PPAR- γ, microtubule-associated protein 1 light-chain 3 (LC3), and p62 which appears in RA synovial fibroblasts. ATO alleviated RA symptoms by boosting effective autophagic flux through significantly downregulating p62, the inflammation and catabolism protein. Importantly, low-dose ATO synergizes with Vitamin D in RA treatment.